The Metaverse as a Virtual Learning Space: Perceptions from the UAE - Abukhalaf, Siham; Charles, Tendai; Hill, Christopher (Journal of Ecohumanism, 2024)
This study investigated stakeholders’ understanding and perceptions of the Metaverse, particularly its potential advantages and challenges in higher education. A mixed-methods triangulation design was used for data collection, incorporating (a) surveys with university students and professors, (b) interviews with leaders and educators, and (c) focus group discussions with undergraduate students. The total sample size was 300 participants, including 232 university students, 62 educators, and 6 educational leaders. Detailed analysis of both quantitative and qualitative data showed that educators and leaders possess a greater understanding of the Metaverse compared to students. However, despite their familiarity with the Metaverse concept, they lack practical experience in its educational application. Similarly, most students also lack experience with the Metaverse and have practical concerns about its use in their studies. Overall, the study reflects stakeholders’ views on the Metaverse in the context of the United Arab Emirates, highlighting a general belief in its potential for university-level teaching and learning.